The level of suicidal thoughts among a sample of Syrian refugees in Jordan - Ziadeh, Ahmed Rashid; Al Momani, Muhammed Ali; Al Momani, Adel Mustafa (Journal of Educational and Psychological Sciences, 2018)
The study aimed at identifying the prevalence of suicidal thoughts among a sample of Syrian refugees in Jordan in the light of some variables such as sex, age, social status, and educational level. The study used the analytical descriptive method. The sample consisted of (374) refugees and refugees, The results showed that the level of suicidal thoughts among a sample of Syrian refugees in Jordan obtained an average of (1.87) with an estimate (average), as well asThe results of a statistically significant differences in the level of suicidal thoughts attributed to the impact of the social situation, and in favor of a class (single) and the absence of statistically significant differences in the level of suicidal thoughts attributed to the impact of gender, age, educational level.
Keywords: suicidal thoughts; Syrian refugees; Jordan